Factors associated with functional status among older adults with colorectal cancer receiving chemotherapy in Thailand: A cross-sectional study - Saimai Tumwijit; Surachai Maninet; Natthasa Thanthitaweewat (Belitung Nursing Journal, 2026)
Background: Older adults with colorectal cancer who undergo chemotherapy are at high risk of functional status decline. Various demographic and physiological factors influence functional status. However, based on the Theory of Unpleasant Symptoms, few studies have examined the relationships among physiological, psychological, and situational factors, symptom experience, and functional status in older adults with colorectal cancer undergoing chemotherapy. Objective: This study aimed to describe functional status and investigate its associated factors among older adults with colorectal cancer undergoing chemotherapy in Thailand. Methods: A cross-sectional study was conducted among 128 older adults with colorectal cancer receiving chemotherapy. Participants were recruited from a cancer hospital in Northeastern Thailand using multi-stage sampling, followed by systematic random sampling with a random digit table. Data were collected between October 2024 and July 2025 using standardized instruments. Data were analyzed using descriptive statistics, Pearson’s product-moment correlation coefficients, and multiple regression analysis. Results: The findings revealed that participants’ functional status was moderate. Pearson’s correlation coefficient analysis showed that body mass index and social support were positively associated with functional status.  Fatigue, depression, and the number of chemotherapy cycles were negatively associated with functional status. Multiple regression analysis showed that fatigue was the strongest factor negatively associated with functional status (β = -0.375, p < 0.001), followed by depression (β = -0.329, p < 0.001). On the other hand, body mass index (BMI) (β = 0.188, p < 0.05) was positively associated with functional status. The model was statistically significant (R2 = 0.409, F(3,124) = 28.590, p < 0.001), which explaining 40.90% of the variance in functional status. Conclusion: These findings suggest that nurses should implement early screening and proactive nursing interventions to reduce fatigue and depression. Such interventions may include optimizing nutritional status at each chemotherapy cycle and providing family support to help this population preserve functional status.